Exploring the determinants of financial well-being in the millennial generation: a systematic literature review (slr) - M. Lambert, Ma. Jesusa Corazon; Md Jusoh, Zuroni; Abd Rahim, Husniyah; Zainudin, Norzalina (Human Resource Management Academic Research Society, 2023)
Financial well-being (FWB) refers to a state of having sufficient resources to lead a comfortable life. Millennials, born between 1980 and 2000, have faced greater financial challenges compared to other generations. This article aims to explore the existing body of knowledge and provide a comprehensive understanding of the factors that impact FWB among millennials. By utilizing the combined PICO (Population, Intervention, Comparison, and Outcome) and SPIDER (Sample, Phenomenon of Interest, Design, Evaluation, Research type) tools, fifteen articles were reviewed, leading to identification of the five key themes influencing FWB among millennials: financial management behaviour, economic literacy, personality traits, socioeconomic environment, and life phase characteristics. Among these factors, economic literacy emerged as the strongest determinant; as it enables individuals to effectively manage their finances leading to greater FWB. Financial management behaviour and economic literacy are also crucial, as they involve skills, motivation, and confidence in applying financial knowledge and understanding. Personality traits, socioeconomic environment and social support from organizations and institutions are additionally influential factors that significantly affect FWB. Overall, this paper highlights the key factors that play a substantial role in determining FWB among millennials. Further research is recommended to validate the identified factors in this study.